Good Luck or Bad Omen: Attitudes Towards the Slender Loris in the City of Bengaluru, India. (May 2023) - Bhaskaran, Varsha; Nagendra, Harini; Gupta, Kaberi Kar
Cities are characterised by social and cultural diversity. The management of urban wildlife requires developing a better understanding of cultural beliefs associated with wildlife in diverse urban settings. We document a range of cultural beliefs associated with the slender loris ( Loris lydekkerianus ), an endemic, nocturnal primate, in the Indian megacity of Bengaluru. Many residents associate the loris with practices such as black magic, and they believe that the animal's call is a bad omen that brings death and misfortune. Others consider it a harbinger of good luck that offers protection to young children. These superstitious beliefs may motivate illegal wildlife trafficking of the loris. Urbanisation has led to changes in these perceptions, and many respondents now report that they consider these beliefs to be old-fashioned superstitions that hold no place in a modern city. This study contributes to knowledge on changing urban attitudes to wildlife, which is vital to developing conservation strategies that involve local residents.